PERSISTENCE OF LEPROSY PREVALENCE RATES IN BRAZIL: A TEMPORAL AND SPATIAL APPROACH BETWEEN 2001 AND 2022 - Souza, Naanda Kaanna Matos de; Lima, Fernanda Cassiano de; Alves, Denis Fernandes; Filho, Luis Abel da Silva; Silva, Viviane Martins da (Hygeia - Revista Brasileira de Geografia Médica e da Saúde, 2025)
This study aimed to identify the areas of concentration of leprosy cases in Brazil through an ecological approach with space/time analysis of notification data in Brazilian municipalities between 2001 and 2022. The case prevalence rate was constructed, and then a spatial analysis was conducted using the Moran Global and Local Indexes. A reduction in prevalence rates and significant variations in the negative direction were observed. In spatial terms, the results reveal a strong positive spatial autocorrelation and significance at 5%, demonstrating that space plays a key role in explaining the contagion and prevalence of the disease. High-High clusters were formed in the North and Midwest regions, while Low-Low clusters were found in nearly the entire South and parts of the Southeast. Furthermore, it is possible to observe a decrease in the number of hyperendemic municipalities, which are regionally concentrated in endemic areas, especially in municipalities in the North, Northeast, and Midwest. Consequently, these findings may support the implementation of measures for identifying, monitoring, treating, and controlling the disease in areas with high leprosy concentration.